Pengaruh Paparan Medan Magnet ELF (Extremely Low Frequency) Terhadap Derajat Keasaman (pH) Udang Vaname - Umayatul Qumairoh; Sudarti Sudarti; Trapsilo Prihandono (Universitas Andalas, 2021)
Medan magnet ELF (Extremely Low Frequency) merupakan spektrum gelombang elektromagnetik, dimana frekuensi yang dimiliki kurang dari 300 Hz dan termasuk radiasi non pengion. Penelitian ini bertujuan untuk mengkaji pengaruh paparan medan magnet ELF (Extremely Low Frequency) terhadap pH udang vaname. Penelitian ini menggunakan jenis penelitian eksperimen dan menggunakan desain penelitian rancang acak lengkap. Ada dua kelompok dalam penelitian ini, yaitu kelompok kontrol yang tidak di papar medan magnet dan kelompok eksperimen yang di papar medan magnet. Pada kelompok eksperimen diberikan perlakuan dengan pemaparan medan magnet Extremely Low Frequency dengan intensitas 300 Î¼T dan 500 Î¼T dan waktu paparan 60 menit, 90 menit, dan 120 menit. Sampel yang digunakan sebanyak 145 sampel udang yang berukuran sama. Kelompok eksperimen ada 120 sampel dan kelompok kontrol ada 25 sampel. Teknik analisis data yang digunakan menggunakan SPSS 22 dengan uji Kruskal-Wallis. Hasil dari teknik analisis data tersebut yaitu paparan medan magnet ELF (Extremely Low Frequency) berpengaruh terhadap pH udang vaname.Â Extremely Low-Frequency magnetic field is a spectrum of electromagnetic waves, where the frequency is less than 300 Hz and includes non-ionizing radiation. This study aims to examine the effect of exposure to ELF (Extremely Low Frequency) magnetic fields on Vannamei shrimp's pH. This research uses experimental research and uses completely randomized design research. This study has two groups: the control group, which is not exposed to magnetic fields, and the experimental group exposed to magnetic fields. The experimental group was given treatment with exposure to Extremely Low-Frequency magnetic fields with an intensity of 300 Î¼T and 500 Î¼T and exposure time of 60 minutes, 90 minutes, and 120 minutes. The samples used were 145 shrimp samples of the same size. The experimental group had 120 samples, and the control group had 25 samples. The data analysis technique used was SPSS 22 with the Kruskal-Wallis test. The result of the data analysis technique is that exposure to an Extremely Low-Frequency magnetic field affects Vannamei shrimp's pH. The pH value of the control group was higher than the experimental group. ELF magnetic exposure can suppress the growth of acid-forming microorganisms in shrimp. It can be proven that the experimental group experienced a significant increase in pH value, while the control group experienced a drastic increase in pH value.